VERBAL TEXT SUPPORTS ON PICTURES IN CREATING DESTINATION IMAGE - Aisyiyah, Siti; Laksman-Huntley, Myrna; Filia, Filia, Dr. (UI Scholars Hub, 2024)
Recently, social media like Instagram, YouTube, and Facebook have been widely used for tourism destination attractiveness. The research investigates how to create a tourism destination image on Instagram from a social semiotic perspective. Data comprises 17 photos of Blue Flame posted by 7 Destination Marketing Organizations (DMOs). Applying the Visual Grammar framework by Kress & Leeuwen (2021), particularly the representational meta function, and Speech Functions by Halliday & Matthiessen (2014), this study finds how verbal texts support visual modes in creating the image of the Blue Flame at Ijen Geopark. Findings show that: (i) Narrative non-transactional action photos are more frequently used to promote the destination image; (ii) Statements delivering praise are most often used to give positive value to the destination; (iii) Narrative non-transactional action pictures attract more viewers’ attention; and (iv) Post with conceptual symbolic photos can evoke viewers’ interest to know more about the destination. Based on the findings, eventhough a picture is the main visual semiotic resource on Instagram, it needs support by verbal resources to make its meaning clearer for viewers. Practical implications of the study and directions for future studies are presented.